Implementation of multicutural islamic religious education values in the development of islamic education institutions - Siti Aminah (At Turots: Jurnal Pendidikan Islam, 2025)
Indonesia is one of the countries with the greatest multicultural potential in the world. This fact can be seen from the dynamics of diverse community life, both in terms of religion, ethnicity, language and culture. The existing diversity can actually be one of the great potentials for the progress of the nation. But on the other hand, it also has the potential to cause various kinds of problems if it is not managed and fostered properly.This research aims to discuss the Implementation of Multicultural Islamic Religious Education Values in the Development of Islamic Education Institutions at Kadiri Islamic University Kediri. In order to obtain data from the results of the study, research was conducted with a qualitative approach and type of case study research. Data collection techniques with participant observation, in-depth interviews and documentation. Data retrieval techniques with snawball sampling techniques. data sources used are primary and secondary. While the data analysis technique uses the Miles and Huberman model. The results of this study indicate that multicultural Islamic education is a response to the development of population diversity in Islamic educational institutions themselves, as well as demands for equal rights for each group. And broadly all learners without distinguishing groups such as gender, ethnicity, race, culture, social strata and religion are entitled to the same education. Then the implementation of Multicultural Islamic Religious Education Values in the Development of Islamic Education Institutions at Kadiri Islamic University Kediri is the Institutional Aspect, Curriculum Aspect and Personnel Aspect.